2014
DOI: 10.1007/s40620-014-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of nephrolithiasis in primary hyperparathyroidism is associated with two polymorphisms of the calcium-sensing receptor gene

Abstract: We conclude that the simultaneous presence of the minor allele at rs1501899 and Arg990Gly may amplify the kidney stone risk in PHPT patients, despite their apparently opposite effects on CASR function in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…In vitro studies showed that the minor G allele at rs67780158 caused a decrease in the transcriptional efficiency of the promoter 1 in two renal cell models 90 . Moreover recent data showed that the simultaneous presence of both rs1501899 and Arg990Gly may potentiate the kidney stone risk in patients with primary hyperparathyroidism despite their apparently opposite effects on CASR function in the kidney 91 .…”
Section: Genetic Polymorphisms Associated With Calcium Nephrolithiasismentioning
confidence: 99%
“…In vitro studies showed that the minor G allele at rs67780158 caused a decrease in the transcriptional efficiency of the promoter 1 in two renal cell models 90 . Moreover recent data showed that the simultaneous presence of both rs1501899 and Arg990Gly may potentiate the kidney stone risk in patients with primary hyperparathyroidism despite their apparently opposite effects on CASR function in the kidney 91 .…”
Section: Genetic Polymorphisms Associated With Calcium Nephrolithiasismentioning
confidence: 99%
“…Moreover, Claudin 14, a protein which regulates the transport of ions ans solutes at epithelial tight junctions, is expressed at a lower level in the rs6776158 GG homozygous subjects. In these cases, nephrolithiasis may occur by another mechanism than hypercalciuria [1, 19]. …”
Section: Calcium-sensing Receptor and Other Diseasesmentioning
confidence: 99%
“…Our searching strategy identified eight papers evaluating the association between CaSR R990G gene polymorphism and the risk of urolithiasis. Of those, four papers [26][27][28][29] showed that R990G gene polymorphism was associated with the risk of urolithiasis with variable odd ratio, ranging from 1.24 to 8.07 (G vs. R). On the other hand, four other studies [30][31][32][33] failed to confirm the correlation.…”
Section: Discussionmentioning
confidence: 99%